1996
DOI: 10.1007/bf03011806
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cisatracurium, a new neuromuscular blocking agent, for tracheal intubation

Abstract: Evaluation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
40
1
6

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 14 publications
8
40
1
6
Order By: Relevance
“…In this study, the onset of action of cisatracurium was signifi cantly lower in the propofol group than in the etomidate group (86.6 ± 14.3 vs 116, 9 ± 11.6 s). These results differ from those described by Bluestein et al 11 , who evaluated the effects of propofol as a hypnotic agent and cisatracurium at varying doses and different times for tracheal intubation. The authors reported that cisatracurium (0.1 mg.kg -1 ) had an onset of action of 4.6 minutes, and tracheal intubation conditions after 2 minutes of injection of NMB were good or excellent in 89% of patients.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In this study, the onset of action of cisatracurium was signifi cantly lower in the propofol group than in the etomidate group (86.6 ± 14.3 vs 116, 9 ± 11.6 s). These results differ from those described by Bluestein et al 11 , who evaluated the effects of propofol as a hypnotic agent and cisatracurium at varying doses and different times for tracheal intubation. The authors reported that cisatracurium (0.1 mg.kg -1 ) had an onset of action of 4.6 minutes, and tracheal intubation conditions after 2 minutes of injection of NMB were good or excellent in 89% of patients.…”
Section: Discussioncontrasting
confidence: 99%
“…In clinical practice, the desirable characteristics in selecting a neuromuscular blocker are hemodynamic stability, rapid onset of action, and ability to provide adequate muscle relaxation to enable laryngoscopy and tracheal intubation 11 . Cisatracurium is one of the 10 isomers of atracurium, with ED 95 of 0.05 mg.kg -1 in balanced anesthesia, without cardiovascular effects due to histamine release, which is an important advantage over atracurium 11,12 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations